Pharmacological insights into Arthrospira platensis (Oscillatoriaceae): Ethnopharmacology, mechanisms, and therapeutic potential in smooth muscle disorders - Diniz, Anderson Fellyp Avelino; Barros, Bárbara Cavalcanti; Silva, João Marcos Araújo da; Arruda, Ray Ravilly Alves; Claudino, Brena Freire de Oliveira; Melo, Michel Benício de; Sousa Filho, José Edvaldo Cavalcanti de; Lacerda Júnior, Francisco Fernandes; Soares, Maxsyara Felismino da Silva; Sousa, Thais Rosa de; Ferreira, Paula Benvindo; Silva, Bagnólia Araújo da (Frontiers in Pharmacology, 2025)
Arthrospira platensis (Oscillatoriaceae) (AP): commonly known as Spirulina, is a widely cultivated cyanobacterium used as both a dietary supplement and a functional food. Growing evidence suggests potential therapeutic effects in smooth muscle–related disorders; however, critical evaluations of the available data remain scarce. This narrative review critically examines preclinical and clinical evidence on Arthrospira platensis and its bioactive metabolites in conditions involving smooth muscle dysfunction, highlighting methodological strengths and limitations, and outlining future research needs. A structured literature search was conducted in PubMed, Scopus, and Web of Science using predefined inclusion criteria, and only studies with validated taxonomy and experimental or clinical data were included. The GA-online Best Practice checklist and the Four Pillars of Best Practice in Ethnopharmacology guided the analysis. Preclinical studies consistently demonstrate antioxidant, anti-inflammatory, and smooth muscle–modulating effects of A. platensis extracts and metabolites, including phycocyanin and polysaccharides. Experimental models in vascular, intestinal, uterine, and airway tissues reveal improved contractility and reduced oxidative damage. Although limited, clinical evidence suggests benefits on metabolic parameters and cardiovascular risk factors. Major limitations include the absence of standardized extract characterization, variable dosing, inconsistent controls, and the scarcity of randomized clinical trials. In conclusion, Arthrospira platensis shows promising pharmacological activities relevant to smooth muscle physiology, but current evidence remains largely preclinical and constrained by methodological weaknesses. Standardized extract characterization, rigorous experimental designs, and adequately powered clinical trials are essential to confirm its therapeutic potential.